Turkish Validity and Reliability Study of the Breast Cancer Survivor Self-Efficacy Scale - Serap Alkaş; Canan Uçakcı-Asalıoğlu; Şengül Yaman-Sözbir (Florence Nightingale Journal of Nursing)
AIM: This study aims to adapt the “Breast Cancer Survivor Self-Efficacy Scale” to Turkish culture and conduct a Turkish validity and reliability study.